Effects of MnSO4 on microstructure and electrical resistance properties of electroless Ni−P thin-films and its application in embedded resistor inside PCB. Issue 2 (29th April 2014) - Zhou, Guoyun; Chen, Chia-Yun; Li, Liyi; Tao, Zhihua; He, Wei; Wong, C.P.
Abstract : Purpose: – Nickel phosphorus (Ni−P) thin-films have been electrolessly deposited in an acid-plating bath with the addition of manganese sulfate monohydrate (MSM) to achieve higher resistance for the application of embedded resistor with value beyond 10 KΩ. As this material is being used for fabricating embedded resistors under the addition of MSM, its resistance properties including effects of MSM concentration and plating time on resistances, temperature coefficient of resistance (TCR), and resistance tolerance of embedded resistor were investigated. The paper aims to discuss these issues. Design/methodology/approach: – The structure of fabricated Ni−P film was detected by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The properties of substrate, including the surface morphologies, glass transition process and boundary of copper pad and substrate surface, were performed by SEM, dynamic mechanical analysis and optical microscope, respectively. The resistance tolerances of embedded resistors were elaborated from the cases of Ni−P thin-film resistance tolerance and the size effects of resistors, respectively. Findings: – The fabricated film was found to be constructed with numerous Ni−P amorphous nanoparticles, which was believed to be the reason of increasing thin-film resistance. The Ni−P thin-films presented over one magnitude order of resistance increasing in the case of MSM concentration varied from 0 to 40 g/L. For the case of TCRs, Ni−P thin-films deposited with 20 g/L MSM exhibited low TCRs of within ±100 ppm/°C Before TR at temperature elevating from 40 to 160°C, indicating that this Ni−P thin-film belongs to the constant TCR materials according to the military standard. For the tolerance of embedded resistor, the tolerance contributed by Ni−P thin-film was obtained to be 9.8 percent, whereas the geometry tolerances were in the range of 0-20 percent according to the geometries of embedded resistor. Originality/value: – For Ni−P thin-film without MSM, its low resistance with around 100 ohm/sq. limit the values of resistor few KΩ and restricted its widespread application of embedded resistor with higher resistance beyond 10 KΩ. The authors introduced MnSO4 in Ni−P electroless plating process to improve the low resistance of Ni−P thin-film. The resistance was increased over one order of magnitude after added with 40 g/L MnSO4 . Due to the specific structure, as this material is being used for fabricating embedded resistors, the electrical properties and its application properties to verify its appliance in embedded resistor were systematically investigated by means of SEM, TEM, XRD characterizations, TCRs, resistance tolerance analysis, respectively.